2003
DOI: 10.1034/j.1399-0039.2003.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a sequence‐based typing system for BoLA‐DRB3 exon 2

Abstract: A rapid, high-resolution sequence-based typing (SBT) system for BoLA-DRB3 exon 2 was developed. Amplification of the entire exon was achieved by a fully nested PCR with locus-specific primers and sequencing was performed directly on the PCR product. Heterozygous sequence data were obtained by automated sequence analysis of both alleles. Forward and reverse sequence data were assembled to improve identification of all heterozygous positions. Specific software (Haplofinder, Roslin Institute Software, Roslin, UK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 35 publications
(47 reference statements)
0
48
0
1
Order By: Relevance
“…marginale based on cELISA [22]. Alleles for the DRB3 gene were determined by direct sequencing of PCR product, using published primers [23]. DNA was extracted from whole blood (Qiagen, Valencia, CA) as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…marginale based on cELISA [22]. Alleles for the DRB3 gene were determined by direct sequencing of PCR product, using published primers [23]. DNA was extracted from whole blood (Qiagen, Valencia, CA) as described above.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from whole blood (Qiagen, Valencia, CA) as described above. The DRB3 alleles were amplified using PCR [23, 24] and the PCR product was sequenced (Eurofins Operon-SimpleSeq, Huntsville, AL). Allele assignment was done using Assign ATF 1.5 (Conexio Genomics, Fremantle, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…The number of BoLA-DRB3 alleles detected in each herd ranged from 9 to 20. By contrast, two cattle (one from JB2 and one from HO1, each carrying three DRB3 alleles as assessed by PCR-SBT and sequencing) were excluded from the study, as this could have resulted from leukochimerism, as previously reported in dizygotic twins (Miltiadou et al, 2003). The alleles with frequencies N5% were DRB3*0201, *0503, *1001, *1101, *1201, *1501 and *1601 in Japanese Black, and DRB3*0101, *1001, *1101, *1201, *1501 and *2703 in Holstein.…”
Section: Distribution Of Bola-drb3 Within the Japanese Black And Holsmentioning
confidence: 96%
“…For the detection of alleles in heterozygous samples, the Aurkisek 2.0 script (Arrieta-Aguirre et al, 2006) was used, which was previously developed by our group and works on HAPLOFINDER (Miltiadou et al, 2003) that assigns alleles to diploid sequences. Thus, a database was generated containing alleles previously cloned.…”
Section: Sequence Alignment and Allele Detectionmentioning
confidence: 99%